A.C. thin film electroluminescence / Tam See Ngah - Tam, See Ngah (Universiti Teknologi MARA, Pahang, 1990)
This article is to summarise basic mechanisms and operating characteristics of A.C. thin electroluminescence (ACFEL) and review its viability as large panel display device.